Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12870-015-0626-y
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA exchange between scions and rootstocks in grafted grapevines

Abstract: BackgroundGrafting has been widely practiced for centuries in the propagation and production of many vegetable and fruit species. However, the underlying molecular and genetic mechanisms for how the graft partners interact with each other to produce a successful graft remain largely unknown. We hypothesized that genome-wide mRNA exchanges, which were recently documented in grafted model plant species, are a general phenomenon widely present in grafted plants, including those in vegetable and fruit species, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 52 publications
9
118
0
3
Order By: Relevance
“…Currently, PlaMoM includes 672 identified mobile ncRNAs (∼3.7%), 16 928 mobile mRNAs (∼94.1%) and 389 mobile proteins (∼2.2%). The mobile macromolecules currently cover 14 different species and ecotypes, namely A. thaliana Col-0, A. thaliana PED (13), Apium graveolens (celery) (15), Antirrhinum majus (snapdragon) (16), Ricinus communis (castor bean) (17), Cucumis melo (melon) (18), Citrullus lanatus (watermelon) (19), Cucumis sativus (cucumber) (19), Cucurbita maxima (pumpkin) (20), Cucurbita moschata (winter squash) (21), Vitis spp (grapevine species) (22), Oryza sativa (rice) (23), Solanum lycopersicum (tomato) (24) and Solanum tuberosum (potato) (11). Identification of the mobile macromolecules was based on different experimental methods, such as analysis of the phloem exudate/sap (15,17,18,25,26), the presence of distinguishable transcripts found in parasitic plants and their host plants (13,14) or by single nucleotide polymorphisms (SNPs) in mRNAs from heterografted plants or from grafted mutant/wild-type plants (13,22,27,28).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, PlaMoM includes 672 identified mobile ncRNAs (∼3.7%), 16 928 mobile mRNAs (∼94.1%) and 389 mobile proteins (∼2.2%). The mobile macromolecules currently cover 14 different species and ecotypes, namely A. thaliana Col-0, A. thaliana PED (13), Apium graveolens (celery) (15), Antirrhinum majus (snapdragon) (16), Ricinus communis (castor bean) (17), Cucumis melo (melon) (18), Citrullus lanatus (watermelon) (19), Cucumis sativus (cucumber) (19), Cucurbita maxima (pumpkin) (20), Cucurbita moschata (winter squash) (21), Vitis spp (grapevine species) (22), Oryza sativa (rice) (23), Solanum lycopersicum (tomato) (24) and Solanum tuberosum (potato) (11). Identification of the mobile macromolecules was based on different experimental methods, such as analysis of the phloem exudate/sap (15,17,18,25,26), the presence of distinguishable transcripts found in parasitic plants and their host plants (13,14) or by single nucleotide polymorphisms (SNPs) in mRNAs from heterografted plants or from grafted mutant/wild-type plants (13,22,27,28).…”
Section: Methodsmentioning
confidence: 99%
“…While the functional role of many mobile mRNAs in distant tissues remains to be elucidated, evidence supports the notion that trafficking of small si/miRNAs and large mRNAs via the phloem plays an important role in regulating plant development (Lucas et al, 2001). A surprisingly high number of mRNAs can be found in phloem exudates (Guo et al, 2013) and move across graft junctions (Thieme et al, 2015;Yang et al, 2015), but no general and easily predictable RNA motif or conserved sequence mediating mobility could be identified in the graftmobile transcript populations (Calderwood et al, 2016). However, our data suggest that a significant fraction of mobile mRNAs carries a TLS motif potentially mediating mobility across graft junctions.…”
Section: Discussionmentioning
confidence: 89%
“…On the one hand, conserved and, thus, predictive mRNA motifs have not been described for known graftmobile mRNA populations (Guo et al, 2013;Thieme et al, 2015;Yang et al, 2015). On the other hand, recent work in potato showed that the 39 untranslated region (UTR) of the phloemmobile transcript BEL5 supports mRNA stability and trafficking into roots, where BEL5 protein initiates tuber formation (Banerjee et al, 2009;Cho et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In grafted grapevines, nearly half of the transmitting genes observed in in vitro grafts (47.4%) were related to the ‘cellular metabolic process’ (Yang et al, 2015). The GO term classification suggested that the DEPs were probably associated with ‘catalytic activity’ (41.0%) and ‘metabolic process’ (40.0%), suggesting that metabolism was involved in the hickory grafting responses ( Figure 2A ).…”
Section: Discussionmentioning
confidence: 99%